THE STUDENT SATISFACTIONS IN USING BMC ONLINE TOOLS IN TEACHING AND LEARNING - Sharmili Mohamed Rafi; Rusliana Binti Rusle (Dinasti Publisher, 2022)
Business Model Canvas (BMC) is a platform of nine building block representing a business. BMC has been adapted to the entrepreneurship syllabus in teaching and learning. However, the BMC Online tools have been developed as a part of the teaching and learning method to easily visualize the nine-building block business model canvas by the student. Hence, the objective of this study is to investigate students’ awareness, self-efficacy, attitude, and helpfulness towards teaching and online learning, particularly the implementation of BMC online tools in Bentong Community College. Questionnaires related to BMC online tools were distributed to Bentong Community College students, involving students from the Business Operations Certificate Programed, and Information Technology Programed. The collected data were analyzed using the Statistical Package for Social Science (SPSS). The results of this study showed that students at the Bentong Community College are aware of the business model online tools and has high satisfaction in the learning process because it is an appropriate platform to create presentations, interact with lecturers, and understand the component of the BMC originally. This study suggests a combined initiative by all relevant parties including course instructors, students, administrators, and college management to provide continuous support in maximizing business model online tools in learning as a new platform in the Pandemic Situation through an online medium at Bentong Community College.